(untitled) (Revista Innova Educación, 2023)
The development of this research was aimed at knowing, using a methodology based on Education 4.0, if that model allows an increase in the percentage of participation of students with an adequate difficulty index in the evaluations. For this, a quantitative - qualitative mixed method was used with a case study implemented in 138 students form the University of Aconcagua (Chile) from September 2022 to July 2023. The instruments to collect the information were checklists of grades and participations (pretest and postest), as well as a complementary survey for the students. The results indicate that the percentage of activities completed increased its mean from 45.1% to 71.3% (p<0.001) with a Cohen’s indicator of 0.89, highlighting a much larger effect size than typical; likewise, the difficulty index in both cases remained in the range of “adequate difficulty” varying slightly form 0.639 to 0.621 with a perception of the students that finally integrates the previous results. It is concluded that the effects of the application of Education 4.0 are positive by promoting active learning and the proper implementation of challenges for the achievement of 21st century skills.